KONSEP METODOLOGI PENDIDIKAN ISLAM KLASIK DAN RELEVANSINYA DENGAN MASA MODERN - Utari, Anggie Sri; Dayantri, Misra Nova; Yulia, Fatma (Universitas Al-Amien Prenduan, 2024)
Classical Islamic education is an educational concept that is deeply rooted in the history of the development of education in the Islamic world, emerging during the golden age of Islamic civilisation with the development of madrasahs and Islamic universities. This educational methodology is based on Islamic religious principles and the teaching of the Quran, using traditional approaches in the learning process. In this challenging modern era, understanding the relevance of classical Islamic education methodology is very important. During the Abbasid Dynasty, teaching methods were categorised into three types: oral, memorised, and written. Oral methods included dictation (direct writing from the teacher), lecture, qira'ah (reading), and discussion. The imla' (writing) method was used at various levels of classical Islamic education. During the time of the Prophet, the methods used included the al-asma' method or lectures. The values of classical Islamic education emphasise the awareness of the individual as a servant of God and a member of society with social responsibilities as well as the ability to manage and utilise God's natural creation.The relevance of classical Islamic methodology to the demands of modern times is increasingly important. The relevance of classical Islamic methodology to the demands of modern times is becoming increasingly important. With the digital revolution and the wide penetration of information technology, Islamic education must be able to utilise these technological tools to increase the effectiveness and accessibility of learning.